Sex and Circadian Rhythm Dependent Behavioral Effects of Chronic Stress in Mice and Modulation of Clock Genes in the Prefrontal Cortex - Mingardi, Jessica; Giovenzana, Mattia; Nicosia, Noemi; Misztak, Paulina; Ieraci, Alessandro; Musazzi, Laura (International journal of molecular sciences, 2025)
Behavioral stress is a recognized triggering factor for systemic diseases, including psychiatric disorders. The stress response is subjected to circadian regulation and many factors shape the susceptibility to its maladaptive consequences, including the biological sex. Accordingly, circadian dysregulation of the stress response, often occurring in a sexually dimorphic manner, is typically associated with psychiatric disorders. However, the interaction between stress, sex, circadian phases, and behavior is still largely unknown. Here, we used the chronic restraint stress (CRS) model in male and female mice to assess the impact of sex and circadian phases on the behavioral consequences of chronic stress. Animals were stressed either in the light or dark phase, and anxious-/depressive-/anhedonic-like behaviors were assessed. Associated transcriptional changes in clock genes were measured in the prefrontal cortex. A significant interaction of stress, sex, and circadian phase was found in most of the parameters evaluated, with no behavioral response to stress in males stressed in the dark phase, and an exaggerated response in females stressed in the dark phase compared to the light phase. We also found some molecular changes in corticosterone serum levels and expression of clock genes in the prefrontal cortex.